Implementasi Metode Pembelajaran Aktif Time Token Terhadap Motivasi Belajar Siswa SD Yapita pada Mata Pelajaran Bahasa Indonesia Kelas 6A - Habib Januar Azharie; Hernik Farisia; Wahyu Hendrawan (Edutama : Jurnal Ilmiah Penelitian Tindakan Kelas, 2024)
Indonesian is taught in grades 1-6 of primary school. Learning is divided into lower and upper grades, with a thematic approach and specialized teaching materials The uniqueness is seen in the thematic approach and teaching materials used. Indonesian language learning in the lower grades aims for students to focus on language skills, understand forms and functions, and use them creatively. This study uses qualitative methods to understand social phenomena from the views of participants. Data was collected from students who conducted teaching assistance at Yapita Surabaya Elementary School for three months. The purpose of the study was to determine the impact of the application of the time token learning method on the motivation of students in class 6A. The research sample consisted of 28 students. The learning strategy encourages changes in the motivation of Yapita Elementary School students in class 6A to learn Indonesian. The time token learning model has advantages in motivating students to participate more independently, improving students' communication skills, and helping students develop habits of listening, sharing, contributing, and accepting criticism. However, the disadvantage of this model is that it can only be used for certain subjects and is not suitable for classes with a large number of students. The steps in time token learning involve conditioning the class for discussion, giving each student a speaking coupon, and awarding points depending on the situation. Students who have used their coupons cannot speak.